Existence and Uniqueness of BV Solutions for a Class of Degenerate Boltzmann Equations with Measures as Initial Conditions (Journal of Partial Differential Equations, 2009)
The existence and uniqueness of the solutions for the Boltzmann equations with measures as initial value are still an open problem which is posed by P. L. Lions (2000). The aim of this paper is to discuss the Cauchy problem of the system of discrete Boltzmann equations of the form ∂_tf_i+(f^{m_i}_i)_x=Q_i(f_1,f_2,...,f_n), (m_i > 1, i=1,...,n) with non-negative finite Radon measures as initial conditions. In particular, the existence and uniqueness of BV solutions for the above problem are obtained.
Keywords: System of discrete Boltzmann equations; BV solutions; existence and uniqueness